Comparative taxonomy of freshwater crabs in peninsular India (Zoological Records and Reviews, 2022)
Freshwater crabs (Crustacea: Brachyura) constitute one of the most diverse and ecologically important invertebrategroups in South Asian river systems, yet their taxonomy in peninsular India remains poorly resolved, with numerousnominal species inadequately described and several cryptic lineages awaiting formal recognition. This study presents acomparative taxonomic assessment of freshwater crabs across peninsular India, based on morphometric analysis of1,847 specimens from 84 collection localities spanning the Eastern Ghats, Western Ghats, and Deccan Plateau,supplemented by molecular phylogenetic analysis of mitochondrial COI and 16S rRNA sequences from 312 individualsrepresenting 58 putative species. Our analyses recover seven family-level lineages represented in peninsular India, withGecarcinucidae constituting the dominant family (32 species, 14 genera). Integrative analysis identifies 8 candidate newspecies and resolves long-standing nomenclatural confusion in the genera Globitelphusa, Ghatiana, andGubernatoriana. Mean COI divergence between morphologically similar but molecularly distinct lineages averages 9.4%,substantially exceeding the barcoding gap threshold and confirming the widespread occurrence of cryptic species in thisgroup. An updated dichotomous key to the freshwater crab genera of peninsular India is provided. Forty-one percent ofassessed species qualify as Threatened under IUCN criteria, with habitat specificity and small range size as primaryvulnerability factors.
Keywords: conservation; Western Ghats; Eastern Ghats; COI barcoding; cryptic species; integrative taxonomy; peninsular India; Gecarcinucidae; Brachyura; freshwater crabs